Multinational Production and Global Shock Propagation during the Great Recession - Haishi Li (Center for Economic Studies and ifo Institute (CESifo), 2023)
Did multinational production (MP) exacerbate or mitigate the collapse of international trade during the Great Recession? What role did MP and trade links play in propagating economic shocks across countries? I resolve the "Multinationals' Resilience Puzzle" during the Great Recession by documenting that while MP declined less than GDP in an average country, MP declined more in larger countries and GDP declined more in countries with a high MP intensity. Thus, MP declined as a percentage of GDP at the global level. To understand the sources of MP and trade collapse, I build a model of MP, trade, and sectoral linkages. The model highlights the frictions that multinational enterprises (MNEs) face when they source from and sell to countries other than their headquarters. These parameters determine MNEs' vertical/horizontal-ness and govern the rich interactions between MP and trade. According to the model with MP, supply-side productivity shocks contributed to the collapse of trade almost as much as demand shocks. The majority of the collapse in MP (both globally and cross-country) was attributed to shocks that affected aggregate productivity and were specific to multinationals in a few key headquarters countries. The MP links significantly amplified the impact of these shocks on the rest of the world, which had a much greater impact than if the shocks had been propagated solely through trade.
Keywords: 330; Internationale Produktion; Außenhandel; Multinationales Unternehmen; Weltwirtschaftskrise; Welt